Paleoproterozoic khondalites in Brazil: a case study of metamorphism and anatexis in khondalites from Itapecerica supracrustal succession of the southern São Francisco Craton. Issue 4 (4th March 2021) - Miranda, Daniel Andrade; Chaves, Alexandre de Oliveira; Dussin, Ivo Antônio; Porcher, Carla Cristine
ABSTRACT: In Brazil, Paleoproterozoic khondalites were recognized in Ceará, Bahia, Goiás, Tocantins, and Minas Gerais. The Itapecerica supracrustal succession in the Southern São Francisco Craton (Minas Gerais) contains sillimanite-cordierite-garnet-biotite gneiss (khondalite) with an anatectic record. The high-grade khondalite preserve representative mineral assemblages of peak and orogen collapse after post-peak decompressional stage. Based on petrographic observations and P–T pseudosections of bulk rock compositions, a clockwise pressure-temperature-time (P–T-t) path was inferred. The metamorphic peak assemblage is liquid + plagioclase ± K-feldspar + garnet + biotite + ilmenite + sillimanite + quartz at 715–772ºC and 5.5–7.5 kbar. In addition, the precursor sediments had mixed pelitic-wacke compositions resulting from erosion of different sources. Sediment deposition would have occurred at active continental marginal setting. Surrounding the khondalite occurs a peraluminous metagranite named here as Água Rasa, formed in syn- to post-collisional setting, whose εNd(t) (−0.5 to −2.7) and 87 Sr/ 86 Sr(t) (1.04 to 1.08) and the data set indicate that the precursor magma of the Água Rasa metagranite originated from anatexis of the khondalitic rocks (crustal source) and associated amphibolites (mantle source) during the crustal thickening followed by tectonic exhumation at peak metamorphism and at decompressional stage during the orogenic collapse. The khondalite yielded ages from monazite U-Th-PbT dating of 2090 ± 26 Ma and 1937 ± 32 Ma, while the Água Rasa metagranite yielded ages of 2077 ± 24 Ma and 1941 ± 23 from monazite and 1934 ± 74 Ma from zircon U-Pb. The ages of >2.0 Ga are related to the metamorphic peak, while the younger ones ( 1940 Ma) are related to the orogen collapse after post-peak decompressional stage. Similarities between the khondalite rocks of this study and of the North China Craton suggest that the São Francisco-Congo Craton was near the North China Craton in the supercontinent Columbia for the 2.1–1.9 Ga period.